CD25 signaling regulates the function and stability of peripheral Foxp3+ regulatory T cells derived from the spleen and lymph nodes of mice. (August 2016) - Wang, Kunpeng; Gu, Jian; Ni, Xuhao; Ding, Zheng; Wang, Qi; Zhou, Haoming; Zheng, SongGuo; Li, Bin; Lu, Ling
Highlights: Spleen-derived Tregs exhibit consistent Foxp3 levels and reduced IL-17A expression. Spleen-derived Tregs exhibit consistent functional activity in the presence of inflammatory cytokines. The CD25 bright Treg subset was more abundant in spleen-derived Tregs. Spleen-derived Tregs, but not lymph node-derived Tregs, protect against hepatic IRI in vivo. Abstract: Regulatory T cells (Tregs) play a critical role in sustaining immune tolerance and maintaining immune balance to alloantigen after transplatation. However, the functions of peripheral Tregs in different organs have not been fully characterized. Here, we showed that spleen-derived Tregs exhibited higher expression of Foxp3, greater suppressive capacity, and lower levels of IL-17A secretion than lymph node-derived Tregs in vitro in the presence or absence of inflammatory cytokines, such as IL-6. We found a higher percentage of CD25 bright Tregs among spleen-derived Tregs than among lymph node-derived Tregs. Additionally, in vivo experiments demonstrated that adoptive transfer of spleen-derived Tregs, but not lymph node-derived Tregs, alleviated ischemia-reperfusion injury. These results reveal novel functions of Tregs derived from peripheral organs. In particular, spleen-derived Tregs, primarily consisting of CD25 bright cells, may provide a more significant contribution to the suppression of immune-mediated autoimmune and inflammatory disease.